In-vitro Characterization of a Hernia Mesh Featuring a Nanostructured Coating - Giuntoli, Giulia; Muzio, Giuliana; Actis, Chiara; Ganora, Alessandro; Calzone, Stefano; Bruno, Matteo; Ciardelli, Gianluca; Carmagnola, Irene; Tonda-Turo, Chiara (Frontiers in Bioengineering and Biotechnology, 2021)
Abdominal hernia repair is a frequently performed surgical procedure worldwide. Currently, the use of polypropylene (PP) surgical meshes for the repair of abdominal hernias constitutes the primary surgical approach, being widely accepted as superior to primary suture repair. Surgical meshes act as a reinforcement for the weakened or damaged tissues and support tissue restoration. However, implanted meshes could suffer from poor integration with the surrounding tissues. In this context, the present study describes the preliminary evaluation of a PCL-Gel-based nanofibrous coating as an element to develop a multicomponent hernia mesh device (meshPCL-Gel) that could overcome this limitation thanks to the presence of a nanostructured biomimetic substrate for enhanced cell attachment and new tissue formation. Through the electrospinning technique, a commercial PP hernia mesh was coated with a nanofibrous membrane from a polycaprolactone (PCL) and gelatin (Gel) blend (PCL-Gel). Resulting PCL-Gel nanofibers were homogeneous and defect-free, with an average diameter of 0.15 ± 0.04 μm. The presence of Gel decreased PCL hydrophobicity, so that membranes average water contact angle dropped from 138.9° ± 1.1° (PCL) to 99.9 ± 21.6°, while it slightly influenced mechanical properties, which remained comparable to those of PCL (E = 15.7 ± 2.7 MPa, σ_R= 7.7 ± 0.6 ε_R = 118.8 ± 13.2%). Hydrolytic and enzymatic degradation was conducted on PCL-Gel up to 28 days, with maximum weight losses around 20% and 40%, respectively. The meshPCL-Gel device was obtained with few simple steps, with no influences on the original mechanical properties of the bare mesh, and good stability under physiological conditions. The biocompatibility of meshPCL-Gel was assessed by culturing BJ human fibroblasts on the device, up to 7 days. After 24 h, cells adhered to the nanofibrous substrate, and after 72h their metabolic activity was about 70% with respect to control cells. The absence of detectable lactate dehydrogenase in the culture medium indicated that no necrosis induction occurred. Hence, the developed nanostructured coating provided the meshPCL-Gel device with chemical and topographical cues similar to the native extracellular matrix ones, that could be exploited for enhancing the biological response and, consequently, mesh integration, in abdominal wall hernia repair.